Syryjsko-libijska walka z syjonizmem w PRL. Zaangażowanie Michela Mounayera w działalność „lewicy” partyjnej w latach 1978–1986 - Gasztold-Seń, Przemysław (Pamięć i Sprawiedliwość, 2010)
The article focuses on the Syrian journalist Michael Mounayer’s commitment to an activity of the party “left” during 1978–1986. The Arabian correspondent, of the “Al-Riada” magazine arrived in Poland in 1964. In 1978 he came in contact with the circle of Ryszard Gontarz, with whom he maintained close ties until his departure from Poland in 1986. A group of people called “the left” embraced an anti-Zionist point of view – but in practice – anti-Semitic. It also criticised both the anticommunist opposition, and the regime for “dogmatic” and “national-communistic” reasons. Mounayer became engaged directly in the political activity of “the left”. He participated in editorial board meetings of the weekly “Rzeczywistość” (“The Reality”), kept in touch and collaborated with the Association of Social and Political Knowledge Clubs “The Reality” (Stowarzyszenie Klubów Wiedzy Społeczno-Politycznej ‘Rzeczywistość’”) and with the “Grunwald” Patriotic Association (Zjednoczenie Patriotyczne “Grunwald”). Furthermore, he provided both groups with financial assistance which meant – Arab support for Polish political organizations fighting against Zionism. Mounayer was truly interested in the Ministry of Internal Affairs’ inner games, as well as in high-ranking party officials of Jewish origin. Apart from this, he gathered information about the Polish United Workers’ Party’s (Polska Zjednoczona Partia Robotnicza, PZPR) factions and coteries. As a consequence, the communist security apparatus started taking an interest in Mounayer’s activity. Ministry of Internal Affairs officers conducted an operational dialogue with him about his political view, contacts with party activists, connections with Syrian and Libyan embassies, and about the Arab diplomats’ interest in “The Jewish problem” in the People’s Republic of Poland (Polska Rzeczpospolita Ludowa, PRL). The publication of two text by Mounayer on Polish – Israeli relations in the London – based Arabic Al-Arab magazine ended his collaboration with “the left” in 1986. It is known that he was incited by the Libyan Embassy to publish them. Both articles criticized Genaral Jaruzelski’s foreign policy and accused the Polish authorities of being pro-Zionist. For the abovementioned reasons Mounayer was forced to leave Polish territory and was put on the Peoples’ Republic of Poland persona non grata list. The diplomatic missions of Syria, Libya and the Palestine Liberation Organization [the BAAS party] as well as high-ranking members of the Arab Socialist Ba’ath Party in Syria with its Vice-President, all interceded with the Polish authorities on behalf of the expelled Mounayer.